Reading Mulk Raj Anand’s Untouchable as a satire on Class Discrimination - N. M. Sri Prasanna, Dr. L. Ronald David (International Journal of Modern Agriculture, 2020)
Mulk Raj Anand is prolific indian writer whose novels bring out the common issues that haunt the society, especially the underprivileged sections of the Indian society . His novel Untouchable portrays the pathetic plight of the under privileged class who are treated like menials with hatred, maltreatment, discrimination that are fuelled by the mainstream society and its belief that foster casteism and communal man-made hierarchy. This novel unearths the cruel practices of the upper class and critically examines the double strandedness of the upper class people which makes this novel a satire on the society in general and upper-class in particular. The novel beautifully displays the experience of a underprivileged boy Bakha who is branded, torn and tortured by the fangs of upper class sentiments, class discrimination and social ostracization, Neverrheless,it exposes the weakness and frailties of the upper class, rendering the novel a satirical tone.